Antagonistic interaction between male‐killing and cytoplasmic incompatibility induced by Cardinium and Wolbachia in the whitefly, Bemisia tabaci. (14th August 2020) - Lv, Ning; Peng, Jing; Chen, Xin‐Yi; Guo, Chang‐Fei; Sang, Wen; Wang, Xing‐Min; Ahmed, Muhammad Z.; Xu, Yong‐Yu; Qiu, Bao‐Li
Abstract: Cardinium and Wolbachia are maternally inherited bacterial symbionts of arthropods that can manipulate host reproduction by increasing the fitness of infected females. Here, we report that Cardinium and Wolbachia coinfection induced male‐killing and cytoplasmic incompatibility (CI) when they coexisted in a cryptic species of whitefly, Bemisia tabaci Asia II7. Cardinium and Wolbachia symbionts were either singly or simultaneously localized in the bacteriocytes placed in the abdomen of B. tabaci nymphs and adults. Cardinium–Wolbachia coinfection induced male‐killing and resulted in a higher female sex ratio in the intraspecific amphigenetic progeny of Asia II7 ICWH and ICWL lines; interestingly, male‐killing induction was enhanced with increased Cardinium titer. Moreover, single infection of Wolbachia induced partial CI in the Asia II7 IW line and resulted in reduced fecundity, higher embryonic mortality, and lower female sex ratio. The uninfected Asia II7 IU line had significantly higher fecundity, lower embryonic and nymphal mortalities, and a lower level of CI than both the Wolbachia‐ infected Asia II7 IW line and the Cardinium–Wolbachia ‐coinfected Asia II7 ICWH line. Our findings indicate that Cardinium–Wolbachia coinfection induced male‐killing, which may have had antagonistic effects on Wolbachia‐ induced CI in the Asia II7 whiteflies. For the first time, our study revealed that B. tabaci Asia II7 reproduction is co‐manipulated by Cardinium and Wolbachia endosymbionts.